The Silent Experiences of Young Bilingual Learners A Sociocultural Study into the Silent Period - Bligh, Caroline (Springer eBooks, 2014)
Many teachers are increasingly concerned with how to best support the learning of the rising numbers of bilingual learners in schools - particularly those children who are new to English and therefore cannot yet communicate with the teacher or their peers in their first language - during the silent period. This book offers an alternative insight to that which is most commonly available to teachers and researchers, as instead of examining language acquisition purely from a linguistic approach; it explores the learning that is occurring through a sociocultural lens and even more significantly, from the young child's perspective - the worm's eye view. Investigated through the experiences of young bilingual learners allows the reader to make sense of the making meaning that occurs when the child cannot make sense of his/her new 'world'; nor communicate verbally in the language of instruction in the classroom. Remarkably, learning through the silent period is revealed as both complex and 'messy' as the bilingual child mediates his or her own learning through a synthesis of alternative learning pathways. The silent period is presented as a crucial time for learning; distributed through a synthesis of close observation, intense listening and most significantly copying the practices of others. Throughout the silent period the children are not only seen to be learning but also contributing to the classroom practices. The book not only initiates new understandings of second language learning, but also offers creative ideas on how to raise the achievement of children who are learning English as an additional language.